Isolation and characterization of eight microsatellite loci in Chaetodon ornatissimus and cross-amplification in a sympatric sister species, Chaetodon meyeri - Di Battista, Joseph; Feldheim, K. (Springer, 2011)
Eight polymorphic microsatellite loci were developed for sister species, Ornate butterflyfish (Chaetodon ornatissimus) and Scrawled butterflyfish (Chaetodon meyeri). All loci were scored from samples collected at geographically distinct locations (C. ornatissimus, N = 37, Republic of Palau; C. meyeri, N = 30, Republic of Kiribati). There were 14.00 or 13.50 mean alleles per locus (A) for C. ornatissimus and C. meyeri, respectively, with observed heterozygosity (H O) ranging from 0.61 to 0.97 and 0.60 to 1.00. Most loci conformed to Hardy-Weinberg expectations, were in linkage equilibrium, and lacked confounding null alleles. We expect these markers to be useful for resolving population structure and patterns of hybridization. © Springer Science+Business Media B.V. 2010.